JURIDICAL PLURALISM IN BRAZILIAN FAVELAS: COMMENTS ON LEGITIMACY - SOUSA BIRNFELD, CARLOS ANDRÉ; VOTTO CRUZ, ARTHUR (Revista do Programa de Pós-Graduação em Direito, 2020)
The Brazilian favelas shelter a large part of the Brazilian population, being largely composed of low-income and socially vulnerable residents, being not only away from the city centers but also from the social interest of the State. From its emergence to the present day, favelas are regarded as areas where formal state law does not arrive, and the lives of residents are run by informal norms, illegal from the point of view of the State and from social groups sometimes democratically instituted and others from criminal organizations that impose themselves with the use of force and violence. The following question that arises from this context of legal pluralism: in a reality of legal pluralism such as that of the Brazilian favelas, are there any alternative legal norms that are endowed with efficacy, acceptance and legitimacy? In order to answer this question, we sought, through the inductive method, the monographic procedure and the bibliographic research technique of the works of Wolkmer, Santos, Barbato Jr, among others, to demonstrate that legal norms developed in favelas whose origin whether in criminal organizations, has the legitimacy to coexist with state norms, as well as to fill the void left by the right of the State by its omission.